Sad Author of Funny Poetry: Edward Lear and Nonsense Poetry - Aliona Matiychak (Pitannâ Lìteraturoznavstva)
The article is devoted to the study of Edward Lear’s art and literary works, in particular his nonsense poetry. The attention is drawn to E. Lear’s role in popularizing the limerick genre form in British and world poetry. The purpose of the article is to analyze humorous poems by Edward Lear in the aspect of genre study. The style of Lear’s versification (his short and silly poetic rhymes) is analyzed. The research of the style and genre specific of his nonsense verses (comic rhymes, puns, paronomasia, creativity in spelling, creating neologisms according to the principles of homophony, his weird creatures and absurd stories, etc.) is carried out. The influence of the poet’s personal features on his creativity is observed with reference to his drawings and illustrations. Psychological and biographical facts are considered in the research and allow understanding the poet’s world outlook.